Minireview and case report: Duplication of the portal vein and combinations - Laura Ziegler (Elsevier, 2021)
This is a minireview and case report on a concurrent duplication of the portal vein and a duplication of the left renal vein. The portal vein system supplies about seventy five percent of the blood for the liver and is involved in the manifestation of several liver diseases such as portal hypertension and portosystemic shunts. The vitelline veins and their anastomoses are involved in this anatomical variation during development. Similar to that also variations or malformations of the renal veins resulted from early primitive structures and their obliteration or non obliteration, respectively. Two rather rare anomalies of two venous systems might have been a coincidence or a common cause.